Metabolic effects of resistance or high-intensity interval training among glycemic control-nonresponsive children with insulin resistance (2018)
Background:Little evidence exists on which variables of body composition or muscular strength mediates more glucose control improvements taking into account inter-individual metabolic variability to different modes of exercise training.Objective:We examined â mediators' to the effects of 6-weeks of resistance training (RT) or high-intensity interval training (HIT) on glucose control parameters in physically inactive schoolchildren with insulin resistance (IR). Second, we also determined both training-induce changes and the prevalence of responders (R) and non-responders (NR) to decrease the IR level.Methods:Fifty-six physically inactive children diagnosed with IR followed a RT or supervised HIT program for 6 weeks. Participants were classified based on 'HOMA-IR into glycemic control R (decrease in homeostasis model assessment-IR (HOMA-IR) less than 3.0 after intervention) and NRs (no changes or values HOMA-IR?43.0 after intervention). The primary outcome was HOMA-IR associated with their mediators; second, the training-induced changes to glucose control parameters; and third the report of R and NR to improve body composition, cardiovascular, metabolic and performance variables.Results:Mediation analysis revealed that improvements (decreases) in abdominal fat by the waist circumference can explain more the effects (decreases) of HOMA-IR in physically inactive schoolchildren under RT or HIT regimes. The same analysis showed that increased one-maximum repetition leg-extension was correlated with the change in HOMA-IR (?=0.058; P=0.049). Furthermore, a change in the waist circumference fully mediated the dose-response relationship between changes in the leg-extension strength and HOMA-IR (??=0.004; P=0.178). RT or HIT were associated with significant improvements in body composition, muscular strength, blood pressure and cardiometabolic parameters irrespective of improvement in glycemic control response. Both glucose control RT-R and HIT-R (respectively), had significant improvements in mean HOMA-IR, mean muscular strength leg-extension and mean measures of adiposity.Conclusions:The improvements in the lower body strength and the decreases in waist circumference can explain more the effects of the improvements in glucose control of IR schoolchildren in R group after 6 weeks of RT or HIT, showing both regimes similar effects on body composition or muscular strength independent of interindividual metabolic response variability. © 2018 Macmillan Publishers Limited, part of Springer Nature.